War exit - Fabre, C (University of Chicago Press, 2015)
This article argues that we must sever the ethics of war termination from the ethics of war initiation: a belligerent who embarks on a just war at time t1 might be under a duty to sue for peace at t2 before it has achieved its just war aims; conversely, a belligerent who embarks on an unjust war at t1 might acquire a justification for continuing at t2. In the course of making that argument, the article evaluates the various ways in which belligerents end their wars.